THE METABOLIC CHARACTERISTICS OF THE LOCOMOTORY MUSCLES OF GREY SEALS (HALICHOERUS-GRYPUS), HARBOR SEALS (PHOCA-VITULINA) AND ANTARCTIC FUR SEALS (ARCTOCEPHALUS-GAZELLA) - REED, J Z; BUTLER, P J; FEDAK, M A (1994)
It is not known precisely how marine mammals are able to maintain muscle function during active swimming in breath-hold dives, when ventilation stops and heart rate falls. Examination of muscle biochemistry and histochemistry can provide information on the relative importance of different metabolic pathways, the contractile potential of the muscle fibres, the oxygen storage capacity of the muscle and the capillary distribution in these animals. In this study, samples of locomotory muscle were taken from wild grey seals (Halichoerus grypus), harbour seals (Phoca vitulina) and Antarctic fur seals (Arctocephalus gazella); Wistar rat muscle was analysed for comparative purposes. Activities of citrate synthase and beta-hydroxyacyl CoA dehydrogenase were higher in the harbour seal muscle than in the grey seal muscle, suggesting that harbour seals have a greater aerobic capacity. Both phocid muscles had a greater reliance on fatty acid oxidation than the fur seal or rat muscles. The myoglobin data demonstrate that the grey seals have the highest oxygen storage capacity of the three pinniped species, which correlates with their greater diving ability. Myoglobin levels were higher in all three pinniped species than in the Wistar rat. The fibre type compositions suggest that the muscles from the fur seals have higher glycolytic capacities than those of the phocid seals [fur seal pectoralis, 7% slow-twitch oxidative fibres (SO), 25% fast-twitch oxidative glycolytic fibres (FOG), 68% fast-twitch glycolytic fibres (FG); grey seal 57% SO, 5% FOG, 38% FG; area per cents]. However, the pectoralis muscle of the fur seal, although the most glycolytic of the pinniped muscles studied, has the highest capillary density, which indicates a high capacity for fuel distribution. These results show that, while pinniped muscle has an increased oxygen storage potential compared with the muscle of a typical terrestrial mammal, there are no distinct adaptations for diving in the enzyme pathways or fibre type distributions of the pinniped ...